1882 W. Va. Acts 421-22, ch. 135, § 1 - (:unkn) unknown (My University, 1882)
Prohibited the carrying of a pistol, dirk, Bowie knife, razor, slungshot, billy, metallic or other false knuckles, or any other dangerous or deadly weapon. Also prohibited selling any such weapon to a minor. Punishable by fine of $25-200 and imprisonment of 1-12 months.
Keywords: CARRY; TRANSFER - MINORS